Exploring Translanguaging and Code-Mixing in Santri Communication in the Pesantren Environment - Dian, Zidna Ilma; Setiyawan, Agung; Fatihin, Muhammad Khairul (STUDI ARAB, 2025)
Intercultural communication in the context of traditional Islamic education ideally prioritizes authentic and structured linguistic expression, with the multilingual proficiency of santri manifested in language practices with clear linguistic boundaries. However, observations at Darullughah Wadda'wah Islamic Boarding School indicate the existence of linguistic distortions characterized by the extensive and nonsystematic use of code-mixing, creating an epistemological gap in the language acquisition and linguistic identity construction of santri. This study uses a descriptive qualitative approach to analyze the phenomenon of code-mixing in santri interactions, focusing on the classification, form, and function of code-mixing. The results identified the existence of outer code mixing in the form of Indonesian-Arabic and Arabic-Indonesian, as well as inner code mixing in the form of Indonesian-Javanese and Javanese-Indonesian. The forms of code mixing include the insertion of words, phrases, and expressions/idioms, with functions including accuracy of meaning, argumentative, communication efficiency, and building intimacy. The findings contribute to the development of sociolinguistic epistemology in the context of traditional Islamic education and provide an empirical foundation for methodological innovation in language learning in pesantren settings, particularly the development of a "translanguaging pedagogy" approach that optimizes multilingual practices as a productive learning resource.